Fiber optic data communication technological trends and advances - DeCusatis, Casimer
This book is an authoritative review of current and future trends in the field of telecommunications. Written by industry experts who are developing leading-edge data communication networks, Fiber Optic Data Communication provides professionals and students alike with a look at emerging technologies and their applications. Four of the chapters have been revised from DeCusatis's best-selling book, Handbook of Fiber Optic Data Communications ; the remaining eight chapters are all new. Seven helpful appendices, a glossary, and a list of technical acronyms are included. This book can stand alone o.